2018
DOI: 10.1029/2018jd029146
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Secondary Ice Processes in Midlatitude Continental Clouds

Abstract: Clouds contribute very large uncertainties to our understanding of Earth's climate system. This is partly attributed to the insufficient predictive abilities of ice formation processes in clouds and the ramifications for the hydrological cycle and climate. To improve predictions of ice particle concentrations in clouds, a better understanding of the relative contributions of ice nucleating particles and secondary ice processes (SIPs) is needed. To address this challenging question, we combine ice nucleation me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 137 publications
(245 reference statements)
0
11
0
Order By: Relevance
“…By following the immediate changes in the gray scale level of a freezing droplet, the freezing events are detected automatically for each individual droplet. A temperature calibration was applied by detection of the liquefaction and eutectic temperatures of solutions with different water activity as described by Reicher et al 59 and Zipori et al 16…”
Section: Weizmann Supercooled Droplets Observation On a Microarraymentioning
confidence: 99%
See 1 more Smart Citation
“…By following the immediate changes in the gray scale level of a freezing droplet, the freezing events are detected automatically for each individual droplet. A temperature calibration was applied by detection of the liquefaction and eutectic temperatures of solutions with different water activity as described by Reicher et al 59 and Zipori et al 16…”
Section: Weizmann Supercooled Droplets Observation On a Microarraymentioning
confidence: 99%
“…10 However, laboratory and field observations are limited, and these secondary processes may only occur at specific temperature and droplet size ranges. [11][12][13][14][15][16] Detailed cloud modeling studies indicate that ice activation should persist over long time to maintain the observed cloud structure and the amount of glaciation. [17][18][19] In other words, continual ice nucleation may explain the observed discrepancy between INP number concentration and the actual ice crystal number concentrations with potential consequences for explaining observed cloud structure and precipitation amount.…”
Section: Introductionmentioning
confidence: 99%
“…This concept is particularly timely given the recent surge in microfluidic platforms being developed for the droplet-based study of ice nucleation, [43][44][45][46][47][48] including for applications such as cryobiology [49][50][51][52][53] and atmospheric science. 34,[54][55][56][57][58][59][60][61][62]…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the role of surface properties and their potential variations 5 under atmospheric conditions remains challenging. For example, the ice nucleation (IN) ability of an ice nucleating particle (INP) may be influenced by the change in surface properties due to aging processes in ice nuclei (Coluzza et al, 2017) or other secondary ice processes (Zipori et al, 2018). Solutes are able to affect freezing (Zobrist et al, 2008) and as recently shown even in minor concentration (Whale et al, 2018).…”
Section: Introductionmentioning
confidence: 99%